2022
DOI: 10.3390/jcm11020451
|View full text |Cite
|
Sign up to set email alerts
|

Right Heart Pulmonary Circulation Unit Response to Exercise in Patients with Controlled Systemic Arterial Hypertension: Insights from the RIGHT Heart International NETwork (RIGHT-NET)

Abstract: Background. Systemic arterial hypertension (HTN) is the main risk factor for the development of heart failure with preserved ejection fraction (HFpEF). The aim of the study was was to assess the trends in PASP, E/E’ and TAPSE during exercise Doppler echocardiography (EDE) in hypertensive (HTN) patients vs. healthy subjects stratified by age. Methods. EDE was performed in 155 hypertensive patients and in 145 healthy subjects (mean age 62 ± 12.0 vs. 54 ± 14.9 years respectively, p < 0.0001). EDE was undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
0
0
1
Order By: Relevance
“…(51) Vriz y colaboradores realizaron ecocardiografía Doppler de ejercicio en un grupo de 155 pacientes hipertensos y en 145 sujetos normales, y documentaron que la TAPSE durante el ejercicio era menor en el grupo hipertenso mientras que la PSAP, así como su valor indexado al volumen minuto alcanzado durante el ejercicio, era mayor. (52) En un análisis llevado a cabo recientemente por nuestro grupo, la mediana y el rango intercuartilo (RIC) de la masa ventricular izquierda fue de 119 (91-155) g/m 2 en pacientes que bebían alcohol [mediana 30 UA por semana] vs. 93 (75-110) g/m 2 en un grupo control que bebía hasta 2 UA por semana, (p = 0,008); y el espesor parietal relativo en el grupo alcohólico fue de 0,5 (0,4-0,6) vs. 0,4 (0,4-0,4) en los controles; p = 0,001. En el mismo estudio, el strain longitudinal global (SLG) y los strain específicos de las capas del corazón mostraron valores absolutos menores en el grupo con abuso de alcohol en comparación con los controles.…”
Section: Miocardiopatía Dilatadaunclassified
“…(51) Vriz y colaboradores realizaron ecocardiografía Doppler de ejercicio en un grupo de 155 pacientes hipertensos y en 145 sujetos normales, y documentaron que la TAPSE durante el ejercicio era menor en el grupo hipertenso mientras que la PSAP, así como su valor indexado al volumen minuto alcanzado durante el ejercicio, era mayor. (52) En un análisis llevado a cabo recientemente por nuestro grupo, la mediana y el rango intercuartilo (RIC) de la masa ventricular izquierda fue de 119 (91-155) g/m 2 en pacientes que bebían alcohol [mediana 30 UA por semana] vs. 93 (75-110) g/m 2 en un grupo control que bebía hasta 2 UA por semana, (p = 0,008); y el espesor parietal relativo en el grupo alcohólico fue de 0,5 (0,4-0,6) vs. 0,4 (0,4-0,4) en los controles; p = 0,001. En el mismo estudio, el strain longitudinal global (SLG) y los strain específicos de las capas del corazón mostraron valores absolutos menores en el grupo con abuso de alcohol en comparación con los controles.…”
Section: Miocardiopatía Dilatadaunclassified
“…(51) Vriz and co-authors performed exercise Doppler echocardiography in a group of 155 hypertensive patients and in 145 healthy subjects, and documented that TAPSE during exercise was lower in the hypertensive group, whereas PASP as well as its value indexed to the cardiac output achieved during exercise was higher. (52) In a recently published analysis of our group, the median and interquartile range (IQR) of left ventricular mass index was 119 (91-155) g/m² in patients drinking alcohol (median 30 AU per week) vs. 93 (75-110) g/m² in a control group (drinking up to 2 AU per week), p = 0.008; and the relative wall thickness in the alcohol group was 0.5 (0.4-0.6) vs. 0.4 (0.4-0.4) in controls, p = 0.001. In the same study, global longitudinal strain (GLS) and layer strains showed lower absolute values in alcohol overusers as compared to controls.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%